Diagnosis of amoebic liver abscess by agar diffusion test: a simple and efficient method with non-axenic antigen (Colombia Medica, 1986)
The agar gel diffusion (AGD) was performed in 38 persons using an antigen obtained from E. histolytica trophozoites cultured directly from feces in Boeck and Drbohlav diphasic medium microbially contaminated. Twenty-two of 38 persons had clinically proven amoebic liver abscess (ALA), 6 had other diseases, and 10 were healthy controls. The test was positive in 19 (86.5%) of the 22 patients with ALA. The six patients with other diseases and 10 healthy controls were negative.Identical AGD results were obtained with an antigen prepared from amebae grown in an axenic medium. Sera were also studied with indirect hemagglutination (IHA) test, which was insignificantly more sensitive but less specific than AGD (IHA sensitivity: 95%). A patient with sickle-cell anemia, but with no evidence of ALA, showed positive results with IHA and negative results with AGD. No false positive results were observed using AGD. Perhaps the most important consideration of the reported experience is that antigen obtained from E. histolytica trophozoites grown in Boeck and Drbrohlav diphasic medium in the presence of intestinal flora proved efficient and reliable in AGD test employed as a serodiagnostic aid for amoebic liver abscess.In addition, the low cost and simplicity are also advantages of the described AGD test. The authors believe that this test provides an alternative serodiagnostic approach accessible to laboratories and clinicians responsible for diagnosing amoebic liver abscesses and other invasive forms of amebiasis in developing countries where commercial kits have proven too expensive or are unavailable.